Scaffolds and design factors to increase creative outcomes in teaching Software Design and Testing - Lee, Chien Sing *; Wong, Daniel K.; Lau, Simon Boung Yew (2015)
Graduates are expected to be able to provide holistic solutions, capable of meeting diverse objectives simultaneously. We aim to investigate how students would conceptualize, make sense, desire to know, find solutions and subsequently progress to collaborate, communicate and create new artefacts. We hypothesize that there would be a higher likelihood of better quality design process, explanations as well as modelling outcomes if first, students can relate between the ability to analyse problems with the ability to conceptualize/model and second, the design of the task focuses on not only functional but more importantly sustaining positive user experience. Findings highlight the importance of key design factors contributing to more creative outcomes.